2020
DOI: 10.2147/dmso.s228229
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resting Whole Body Energy Metabolism in Class 3 Obesity; from Preserved Insulin Sensitivity to Overt Type 2 Diabetes</p>

Abstract: Context: Insulin resistance and diabetes may influence separately or in combination whole body energy metabolism. Objective: To assess the impact of insulin resistance and/or overt type 2 diabetes on resting energy expenditure (REE) in class 3 obese individuals. Design and Setting: Retrospective, cross-sectional analysis of a set of data about individuals attending the outpatients service of a single center of bariatric surgery between January 2015 and December 2017. Patients: We screened 382 patients in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Therefore, the overall risk of stroke and ischemic stroke has significantly increased. 29 A study found that the majority of young type 2 diabetes mellitus patients were obese, 30 and the increased IMT in young adults was associated with obesity. 31 Type 2 diabetes mellitus in youth becomes quickly aggressive after its onset, as the rate of functional impairment in the islet B cells occurs relatively quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the overall risk of stroke and ischemic stroke has significantly increased. 29 A study found that the majority of young type 2 diabetes mellitus patients were obese, 30 and the increased IMT in young adults was associated with obesity. 31 Type 2 diabetes mellitus in youth becomes quickly aggressive after its onset, as the rate of functional impairment in the islet B cells occurs relatively quickly.…”
Section: Discussionmentioning
confidence: 99%
“…The present data suggest that the impact of having a high body mass on REE becomes most influential when both body mass and insulin resistance are severely high. Baseline data from bariatric surgery patients with Class III obesity showed that those with insulin resistance had a higher REE than those who were insulin-sensitive, even when adjusted for fat-free mass [ 43 ]. Both the HOMA-IR score and TG/HDL ratio were significantly higher in participants with Class III obesity compared to those with Class I/II obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The present study observed, in accordance with HOMA-IR criteria adopted to classify obesity phenotype, the prevalence of MUHO was higher than MHO in our population. Studies suggest that MUHO is characterized by a lower inflammatory cytokine environment than MHO [23][24][25] and the last phenotype may be caused by several mechanisms, 26 including preserved insulin sensitivity, specific fat distribution with low visceral and ectopic fat accumulation compared with subcutaneous fat depots, normal adipose tissue function defined by lower adipocyte size, less macrophage infiltration into adipose tissue, 27 and normal adipokine secretion. 26,28 However, more studies are necessary to identify the mechanisms that promote a healthy metabolic profile in individuals with obesity.…”
Section: Discussionmentioning
confidence: 99%